Nutritional Relationship with Acne Vulgaris - Begümhan Ömeroğlu Yel; Fatma Esra Güneş (Hacettepe University, 2018)
Acne is a long-standing inflammation of the hair-oil gland structure. Although the causes of acne are not fully known, there is a relationship between acne and nutrition. Because the diet can change the amount and content of sebum secretion in the skin. Objective: The purpose of this review is to discuss the effects of nutrients and nutrients (milk and dairy products, green tea, dietary glycemic load glycemic index, fatty acids, antioxidants, vitamin A and zinc) on the course of acne vulgaris. Consumption of milk, contributes to the formation of acne. The use of polyphenol extracts obtained from green tea in the treatment of acne reduced the the number of acne. A diet with low glycemic index-glycemic load has been found to cause a significant reduction in acne severity. Inadequate consumption of essential fatty acids leads to inadequate sebum production in the skin. Serum malondialdehyde and serum glutathione peroxidase levels were reported to be lower in individuals with acne complaints. Low A vitamin levels may be a risk factor for acne and acne lesions. It is also stated that serum zinc levels of individuals with acne complaints are significantly lower. Conclusion: Milk restriction for people with acne complaints, consumption of green tea, low glycemic indexglycemic diet can be recommended. It may also be advisable to pay attention to the fat content of foods and the intake level of essential fatty acids. The use of vitamins A and E with vitamins A and B may show therapeutic supportive effects.